Creation of a quick and sensitive fluorescent immunosensor for detecting the mineralocorticoid steroid hormone aldosterone. Issue 221 (July 2022) - Liang, Jingru; Dong, Hang; Wang, Hongsheng; Yi, Zhengjun; Jiang, Guosheng; Inagaki, Takashi; Gomez-Sanchez, Celso E.; Dong, Jinhua; Ueda, Hiroshi
Abstract: Aldosterone (ALD) is a steroid hormone secreted by the zona glomerulosa of the adrenal cortex that mainly acts on the kidney to regulate sodium ion and water reabsorption. Detection of ALD plays an important role in the diagnosis of primary aldosteronism in patients with hypertension. For the first time, the gene encoding the anti-ALD antibody, A2E11, was successfully cloned and analyzed using phage display technology. The antibody had an affinity of 2.5 nM against ALD, and after binding to ALD, it reached saturation within 5 s. Using this antibody, a Quenchbody (Q-body) was constructed by labeling the N-termini of heavy and light chains of the antigen-binding fragment of A2E11 with the fluorescent dye ATTO520 to detect ALD based on the principle of photoinduced electron transfer. The sensor detected ALD in 2 min, and the limit of detection was 24.1 pg/mL with a wide detection range from 24.1 pg/mL to 10 µg/mL and a half-maximal effective concentration of 42.3 ng/mL. At the highest concentration of ALD in the assay, the fluorescence intensity increased by 5.0-fold compared to the original fluorescence intensity of the Q-body solution. The Q-body could be applied to analyze 50% of human serum without a significant influence of the matrix. The recoveries of ALD in spiked serum samples with the Q-body assay were confirmed to range from 90.3% to 98.2%, suggesting their potential applications in the diagnosis of diseases, such as essential hypertension. Graphical Abstract: ga1 Highlights: Detection of aldosterone plays an important role in the diagnosis of aldosteronism. Conventional aldosterone (ALD) assays were time and labor consuming. The gene for anti-ALD antibody genes were cloned using phage display technology. It was successfully used to construct fluorescence quenching-based biosensor Q-body. The sensor detected ALD in 2 min with a wide working range even in serum.